English language teachers’ conceptions of assessment - Muianga, Felizardo (Frontiers in Education, 2023)
Conceptions of assessment are critical to implementing new assessment policies since they influence how teachers understand, interpret, and implement new policies. This small-scale qualitative study investigated 12 secondary school English language teachers’ views about the current secondary school assessment policy and their conceptions of assessment. The data were collected through in-depth interviews in Maputo, Mozambique. The findings suggest that most participants are unfamiliar with the current assessment policy. The participants conceive of assessment as extrinsically motivating students, improving teaching and learning, holding students accountable, reporting, compliance, and irrelevant. Some participants reported pure conceptions of assessment (either improvement or student accountability), while others reported mixed conceptions (either mixed school and student accountability and improvement and mixed student accountability and irrelevant). The emerging profiles of teachers’ conceptions of assessment are expected to provide a starting point for a discussion about designing effective professional development programs in assessment literacy in Mozambique.